Feasability of Open Schooling in Disturbed Areas: A Case Study of Afghanistan - Sushmita Mitra (Commonwealth of Learning, 2014)
Most countries have enshrined right to education in their constitution but in reality to fulfil this commitment countries do face a number of challenges. And this is true with the Islamic Republic of Afghanistan, which unlike other countries has a long history of war, conflicts, insurgency and hence insecurity. Although there have been positive steps towards rehabilitation of the education system and signs of promises can be seen in its achievements, access to quality education remains inequitable particularly across the provinces as a result of remoteness and geographical isolation, harsh climate, insecurity which impedes growth and sustainability of access points, high gender gap in all sectors of education particularly from lower secondary stage to higher stages of education, poor infrastructure prevalent in most schools, untrained teachers and low number of female teachers affecting participation, retention and continuity of studies.